Asymmetric cell division of hematopoietic stem cells: recent advances, emerging concepts, and future perspectives - Nunes, Jessica; Loeffler, Dirk (Frontiers in Hematology, 2024)
Hematopoietic stem cells (HSCs) can self-renew and differentiate for the entire life of an organism to produce new blood cells when needed. This process is regulated by asymmetric cell division (ACD), an evolutionarily conserved mechanism whereby cell fate determinants are unequally segregated into the daughter cells during division to instruct different cell fates. After many years of controversy, recent technical advances in microscopy, imaging, and bioinformatics make it now possible to visualize and quantify how factors segregate asymmetrically in dividing HSCs and lead to predictable changes in daughter cell fates many days later. While the molecular processes behind ACD in HSCs are still poorly understood, accumulating evidence suggests that lysosomes and other organelles, including mitochondria, autophagosomes, mitophagosomes, and recycling endosomes can segregate asymmetrically and act as cell fate determinants during divisions. Asymmetric segregation of lysosomes and mitochondria has been shown to predict mitochondrial activity, translation, and differentiation of HSC daughter cells and their offspring. This discovery and recent seminal findings show that lysosomes, once considered to be merely the trash bin of the cell, regulate many aspects of HSC biology and are crucial for the maintenance of quiescence and stem cell function. Here we provide a historical perspective and discuss the recent advances in our understanding of ACD and the role of lysosomes in HSC function. We discuss the limitations of past studies, talk about emerging concepts, and suggest critical next steps required to move the field forward.